Hybridism in the Instrumental Music of the Medusa Group: Association of Different Musical Genres in Pé no chão (Per Musi, 2013)
In the 1980s, jazz fusion had great international repercussion. In Brazil, it was seen as a symbol of modernity and considered by critics as being a musical forefront, influencing significantly instrumental music groups. This study focuses on the musical production of the Medusa Group, formed in São Paulo by renowned Brazilian popular musicians. The purpose of this article is to understand, through a rhythmic, melodic, harmonic and structural analysis of the song Pé no Chão (Feet on the Ground), the way in which the Group Medusa blends musical elements of Brazilian and American popular styles, obtaining an hybrid sound. It also tries to identify appropriations of musical procedures from fusion, performed in the song.